Penerapan Pohon Rentang Minimum pada Graph dalam Segmentasi Citra - Silvia Alvini; Armiati Armiati; Meira Parma Dewi (Journal of Mathematics UNP, 2021)
Abstract – Image segmentation is the process of separating the object from the background or of other objects that are not a concern, so the object can be processed for the other purposes. Along with the development of technology in digital image processing application, the segmentation process becomes increasingly necessary. The results of the segmentation must be accurate so that any error does not happen in the interpretation of information from an image. This article discussed the application of the minimum spanning tree on a graph in a segment of an image. This method is able to separate an object from the background so that it produces binary image, which is in this case, the object that being the focus is set in white, while the background is black or otherwise. The whole processes were done by using the Matlab R2013a. Keywords – graph, minimum spanning tree, image segmentation, digital image